2019
DOI: 10.14740/cr884
|View full text |Cite
|
Sign up to set email alerts
|

A Simplified Risk Scoring System to Predict Mortality in Cardiovascular Intensive Care Unit

Abstract: Background Cardiovascular intensive care unit (CICU) is an area with high mortality rates globally. The prediction of inpatients mortality risk at CICU needs a simplified scoring systems. Hence, this study aims to analyze the predictors for in-hospital mortality of patients whom hospitalized at CICU of Sardjito General Hospital Yogyakarta and to create a mortality risk score based on the results of this analysis. Methods Data were obtained from SCIENCE (Sardjito Cardiov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…An ideal scoring system would be accurate, easy to use, and simple, as well as minimally intrusive and low-cost. However, no scoring system is flawless, and each one has its own set of limitations, which is why studies are being conducted to enhance accuracy, verify existing ones, and develop new ones [15,16]. Therefore, the aim of our study was to assess and compare the diagnostic accuracy of the PRISM III and the p-SOFA for the prediction of mortality in critically ill children.…”
Section: Introductionmentioning
confidence: 99%
“…An ideal scoring system would be accurate, easy to use, and simple, as well as minimally intrusive and low-cost. However, no scoring system is flawless, and each one has its own set of limitations, which is why studies are being conducted to enhance accuracy, verify existing ones, and develop new ones [15,16]. Therefore, the aim of our study was to assess and compare the diagnostic accuracy of the PRISM III and the p-SOFA for the prediction of mortality in critically ill children.…”
Section: Introductionmentioning
confidence: 99%
“…During this time period, only data from the first 24 h of CICU admission were included. Based on the results of a previous study, 8 the study will need to recruit minimum of 125 subjects with a type I error of 0.05 and with at least 80% power of this study.…”
Section: Methodsmentioning
confidence: 99%
“…Acute coronary syndrome (ACS) constituted the highest proportion of cardiovascular disease in Indonesia. Bagaswoto, et al, observed in SCIENCE (Sardjito Cardiovascular Intensive Care), that from 595 patients coming to the intensive care unit around January to November 2017, 69.9% were diagnosed with ACS and had an in-hospital mortality rate of 9.2% [ 11 ]. In a separate research conducted by Qanitha et al, it was revealed that approximately 76% of individuals within the coronary artery disease (CAD) population were afflicted by ACS during their study period spanning from February 2013 to December 2014 [ 12 ].…”
Section: Introductionmentioning
confidence: 99%